DUNIA ISLAM DIANTARA RIVALITAS AMERIKA SERIKAT DAN TIONGKOK - Ramdhan Muhaimin; Nizar Umar; Dinda Ayuningtyas (Dauliyah: Journal of Islam and International Affairs, 2022)
This article discusses the dynamics of the rivalry between the United States and China in the last decade, as well as its influence on the Islamic world. Globally, the increasing of China’s influence has fueled tensions with the United States (US). Especially since China declared a project of global economic-politic called One Belt One Road (OBOR) in 2013. The ‘New Cold War’ between US and China today has spread to various issues, from trade, cyber-technology, military, and health. This study uses a qualitative method in which content analysis is based on data obtained from news documents, articles and reports. From this research, it is concluded that the dynamic phenomenon in the Islamic world, such as the normalization of Arab-Israeli, the joining of Iran to the SCO, the issue of the Uighur Muslim ethnicity, the Rohingya ethnic minority, the rejection of China's vaccine, and the declaration of defense of AUKUS alliances. Based on the neorealism approach in this study, the dynamics of the international structure affect the behavior of Muslim countries in making their rational choices.